Formulation Optimization and Antibacterial Activity of Citronella (Cymbopogon nardus (L.) Rendle) Topical Gel Spray Against Staphylococcus aureus Using a Simplex Lattice Design - Rajab, Muhammad Andy; Putri, Chintiana Nindya; Suryani, Arman; Salamah, Nina (Jurnal Mandala Pharmacon Indonesia, 2025)
Atopic dermatitis is skin inflammation in the form of dermatitis caused by Staphylococcus aureus bacterial infection. Citronella essential oil has the potential as an active ingredient in spray gel preparations to help overcome atopic dermatitis due to Staphylococcus aureus bacterial infection. The aim is to determine the optimal spray gel formula from citronella essential oil (Cymbopogon nardus (L.) Rendle) and antibacterial activity against Staphylococcus aureus bacteria. The methods material optimized are Na-CMC, Propylene glycol, and tween 20. Evaluation of the preparation in the form of organoleptic tests, homogeneity, pH, viscosity, drying time, spraying patterns, yeast mold numbers using the spread plate method, and antibacterial activity against Staphylococcus aureus bacteria using the good diffusion method. The results of the concentration of Na-CMC: Propylene glycol: Tween 20 (0.27: 4.72: 10) produced an optimal preparation formula. The spray gel is milky white, has a distinctive lemongrass odor, and is slightly thick. The spray gel is homogeneous with a pH of 4.94 ± 0.16, a viscosity of 76.73 ± 7.01 cPs, and a drying time of 3.60 ± 0.40 minutes. The mold/yeast count test showed that the spray gel was free from mold/yeast contamination and was stable at storage temperatures of 4?C and 40?C. The results of antibacterial activity were able to inhibit Staphylococcus aureus bacteria with an inhibition zone diameter of 6.85 mm ± 2.80. Conclusion: Na-CMC concentration of 0.27%, Propylene Glycol concentration of 4.72%, and Tween 20 concentration of 10% produced optimal spray gel and inhibited Staphylococcus aureus.